Persepsi Siswa Terhadap Penerapan Model Contextual Teaching and Learning (CTL) Pada Kurikulum Merdeka (Kumer) Pendidikan Agama Islam (PAI) dan Budi Pekerti Kelas IV di SDN 14 ATTS Kota Bukittinggi - Leonica, Mayang; M, Iswantir (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This learning model is considered an efficient learning model to be used in implementing learning. with data sources, namely teachers teaching Islamic Religious Education subjects and students at SDN 14 ATTS Bukittinggi City. The results of the research show that the Contextual Teaching and Learning learning model starts from learning planning including designing the Learning Implementation Plan by the teacher then implementing learning which is carried out systematically and structured in accordance with the learning plan, then assessment instruments which include three aspects of assessment, namely assessment of activeness, assessment assignments and assessment of student attendance. Students' perceptions of the CTL learning model in grade IV Islamic Religious Education at SDN 14 ATTS Bukittinggi City, namely, 85% of students Strongly Agree (SS) with learning using this CTL model. Meanwhile, 15% of other students chose to agree with this CTL learning model. Disagree (TS) 0%. It can be concluded that the majority of students chose Strongly Agree (SS), namely 85%. This proves that using the CTL model can make students more active and enthusiastic in the learning process. The obstacle to implementing the CTL learning model in Islamic Religious Education is that there are inclusive children in the class where it is difficult for these children to think actively like other general children.